Measurement of the production cross section of prompt Ξ0c baryons at midrapidity in pp collisions at √s = 5.02 TeV - Acharya, Shreyasi (2021)
The transverse momentum (pT) differential cross section of the charm-strange baryon Ξ 0 c is measured at midrapidity (|y| < 0.5) via its semileptonic decay into e +Ξ −νe in pp collisions at √ s = 5.02 TeV with the ALICE detector at the LHC. The ratio of the pT-differential Ξ 0 c -baryon and D0 -meson production cross sections is also reported. The measurements are compared with simulations with different tunes of the PYTHIA 8 event generator, with predictions from a statistical hadronisation model (SHM) with a largely augmented set of charm-baryon states beyond the current lists of the Particle Data Group, and with models including hadronisation via quark coalescence. The pT-integrated cross section of prompt Ξ 0 c -baryon production at midrapidity is also reported, which is used to calculate the baryon-to-meson ratio Ξ 0 c/D0 = 0.20 ± 0.04 (stat.) +0.08 −0.07 (syst.). These results provide an additional indication of a modification of the charm fragmentation from e +e − and e −p collisions to pp collisions.